2018
DOI: 10.1177/2192568218776609
|View full text |Cite
|
Sign up to set email alerts
|

Does Addition of Tobramycin Powder Reduce Infection Rates After Spine Surgery?

Abstract: Study Design: Retrospective chart review.Objectives: To evaluate the efficacy of tobramycin and vancomycin powder in reducing surgical site infections in posterior lumbar instrumented fusion. Methods: A multicenter, electronic database search was conducted for all patients who underwent posterior instrumented lumbar fusions.Results: The addition of vancomycin powder decreased postoperative infections from an incidence of 5.7% down to a rate of 2.0%. This difference was statistically significant (P ¼ .018). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A small number of spine surgery studies have suggested that the addition of Gram-negative coverage, such as the use of tobramycin, is required to reduce the SSI rate 11,18 . However, Lee et al recently evaluated the addition of topical tobramycin and found no difference in rates of infection 19 . With these conflicting reports, the Major Extremity Trauma Research Consortium group designed the Local Antibiotic Therapy to Reduce Infection After Operative Treatment of Fractures at High Risk of Infection (VANCO) trial as a high-quality prospective randomized controlled study to evaluate the efficacy of topical vancomycin in orthopaedic trauma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of spine surgery studies have suggested that the addition of Gram-negative coverage, such as the use of tobramycin, is required to reduce the SSI rate 11,18 . However, Lee et al recently evaluated the addition of topical tobramycin and found no difference in rates of infection 19 . With these conflicting reports, the Major Extremity Trauma Research Consortium group designed the Local Antibiotic Therapy to Reduce Infection After Operative Treatment of Fractures at High Risk of Infection (VANCO) trial as a high-quality prospective randomized controlled study to evaluate the efficacy of topical vancomycin in orthopaedic trauma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They found considerable variation among all factors, demonstrating no clear consensus on SSI prevention in shoulder arthroplasty even among a homogenous group of surgeons 28 To combat SSI the intraoperative usage of topical antibiotic powder has gained considerable attention. Previous studies have investigated the use of topical vancomycin, [42][43][44] gentamicin, 45 and tobramycin 46 for a range of orthopedic surgical indications. Vancomycin is the most commonly utilized local antibiotic in powder form within orthopedic surgery and has been the source of multiple previous studies on prevention of SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…Vrabec et al 14 evaluated the local concentration of tobramycin in an in vivo study and found that local tobramycin bone cement can be used to obtain short-term supratherapeutic local concentrations in the surgical site while maintaining minimum serum tobramycin levels. A recent study proved that the topical application of tobramycin combined with vancomycin powder further reduced the infection rate than vancomycin alone 15 .…”
Section: Introductionmentioning
confidence: 99%